Review: Isabelle Stengers, In Catastrophic Times: Resisting the Coming Barbarism. (December 2017) - Beuret, Nicholas
In Catastrophic Times: Resisting the Coming Barbarism (2015) offers a welcome intervention into the current state of global political impasse and ecological catastrophe. Less a cautionary tale or a series of political injunctions, In Catastrophic Times sets out a clear account of how the 'cold panic' induced by looming ecological crises such as climate change is actively produced by the managers of the status quo – those Stengers calls 'Guardians'. Stengers claims it is the convergence of governance without legitimacy with enclosed knowledges and the cult of expertise that has produced a general state of panicked political impotence. Against this mode of governance, Stengers offers a series of tactical experiments, from paying attention as intervention to acts of scientific commoning, articulated through what she calls the GMO event, that seek to seize environmental issues and sociotechnical problems as political questions in order to resist the devolution of modernity into a global social apartheid state.